Understanding the optical properties of doped and undoped 9-armchair graphene nanoribbons in dispersion - Lindenthal, Sebastian; Fazzi, Daniele; Zorn, Nicolas; El Yumin, Abdurrahman Ali; Settele, Simon; Weidinger, Britta; Blasco, Eva; Zaumseil, Jana (ACS nano, 2023)
Graphene nanoribbons are one-dimensional stripes of graphene with width- and edge-structure-dependent electronic properties. They can be synthesized bottom-up in solution to obtain precise ribbon geometries. Here we investigate the optical properties of solution-synthesized 9-armchair graphene nanoribbons (9-aGNRs) that are stabilized as dispersions in organic solvents and further fractionated by liquid cascade centrifugation (LCC). Absorption and photoluminescence spectroscopy reveal two near-infrared absorption and emission peaks whose ratios depend on the LCC fraction. Low-temperature single-nanoribbon photoluminescence spectra suggest the presence of two different nanoribbon species. Based on density functional theory (DFT) and time-dependent DFT calculations, the lowest energy transition can be assigned to pristine 9-aGNRs, while 9-aGNRs with edge-defects, caused by incomplete graphitization, result in more blue-shifted transitions and higher Raman D/G-mode ratios. Hole doping of 9-aGNR dispersions with the electron acceptor F4TCNQ leads to concentration dependent bleaching and quenching of the main absorption and emission bands and the appearance of red-shifted, charge-induced absorption features but no additional emission peaks, thus indicating the formation of polarons instead of the predicted trions (charged excitons) in doped 9-aGNRs.